Effect of Li doping on conductivity and band gap of nickel oxide thin film deposited by spin coating technique. (9th December 2019) - J, Arunodaya; Sahoo, Trilochan
Abstract: Nickel oxide, a stable inorganic p-type semiconductor with wide bandgap is an attractive hole transport material for the perovskite-based solar cells. Doping the nickel oxide with group-1 elements such as lithium, sodium, and potassium is found to increase the conductivity of the film. In the present work lithium doped and undoped nickel oxide thin films are coated on the glass substrate by spin coating method under ambient conditions, and the effects of doping are investigated. The structural, electrical and optical properties have been studied for different doping concentrations. X-ray diffraction confirms the formation of single-phase cubic nickel oxide. It is found that the conductivity increases nine times as the lithium concentration increases. The UV–vis spectroscopy measurement modulates the bandgap with the increase in the lithium-ion concentration.